Treatment with dimethyl fumarate reduces the formation and rupture of intracranial aneurysms: Role of Nrf2 activation. Issue 5 (May 2020) - Pascale, Crissey L; Martinez, Alejandra N; Carr, Christopher; Sawyer, David M; Ribeiro-Alves, Marcelo; Chen, Mimi; O'Donnell, Devon B; Guidry, Jessie J; Amenta, Peter S; Dumont, Aaron S
Oxidative stress and chronic inflammation in arterial walls have been implicated in intracranial aneurysm (IA) formation and rupture. Dimethyl fumarate (DMF) exhibits immunomodulatory properties, partly via activation of the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway which reduces oxidative stress by inducing the antioxidant response element (ARE). This study evaluated the effects of DMF both in vitro, using tumor necrosis factor (TNF)-α-treated vascular smooth muscle cells (VSMC), and in vivo, using a murine elastase model to induce aneurysm formation. The mice were treated with either DMF at 100 mg/kg/day P.O. or vehicle for two weeks. DMF treatment protected VSMCs from TNF-α-induced inflammation as demonstrated by its downregulation of cytokines and upregulation of Nrf2 and smooth muscle cell markers. At higher doses, DMF also inhibited the pro-proliferative action of TNF-α by increasing apoptosis which protected the cells from aponecrosis. In mice, DMF treatment significantly decreased the incidence of aneurysm formation and rupture, at the same time increasing Nrf2 levels. DMF demonstrated a neuroprotective effect in mice with a resultant inhibition of oxidative stress, inflammation, and fibrosis in the cerebrovasculature. This suggests a potential role for DMF as a rescue therapy for patients at risk for formation and rupture of IAs.